(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The “Karakalpak Film” studio, which has a half-century history, has produced and screened films of various genres. Every produced film product reflects the image of that era. It propagates the ideology of that era. The most important thing is that if there were scientific researches on the role of documentaries and their specific features distinguishing them from other media outlets it would be a new step in the development of modern Karakalpak cinema. The article provides a brief history of documentary film in Karakalpakstan and an overview of the shortcomings, as well as the success of the desired documentaries in recent years.